Rational design of porous poly(ethylene glycol) films as a matrix for ssDNA immobilization and hybridization - Zhao, Zhiyong; Das, Saunak; Zharnikov, Michael (Bioengineering, 2022)
Poly(ethylene glycol) (PEG) films, fabricated by thermally induced crosslinking of amine- and epoxy-terminated four-arm STAR-PEG precursors, were used as porous and bioinert matrix for single-stranded DNA (ssDNA) immobilization and hybridization. The immobilization relied on the reaction between the amine groups in the films and N-hydroxy succinimide (NHS) ester groups of the NHS-ester-decorated ssDNA. Whereas the amount of reactive amine groups in the films with the standard 1:1 composition of the precursors turned out to be too low for efficient immobilization, it could be increased noticeably using an excess (2:1) concentration of the amine-terminated precursor. The respective films retained the bioinertness of the 1:1 prototype and could be successfully decorated with probe ssDNA, resulting in porous, 3D PEG-ssDNA sensing assemblies. These assemblies exhibited high selectivity with respect to the target ssDNA strands, with a hybridization efficiency of 78-89% for the matching sequences and full inertness for non-complementary strands. The respective strategy can be applied to the fabrication of DNA microarrays and DNA sensors. As a suitable transduction technique, requiring no ssDNA labeling and showing high sensitivity in the PEG-ssDNA case, electrochemical impedance spectroscopy is suggested.
Gesehen am 18.10.2022